THE ROLE OF SOCIAL MEDIA IN CULTURAL IDENTITY FORMATION: A LITERATURE REVIEW - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2025)
This research aims to examine the role of social media in cultural identity formation through a comprehensive literature review. Social media has become an important platform for cultural preservation and promotion, allowing individuals and communities to share and celebrate their cultural heritage with a wider audience. In addition, social media supports the creative expression of cultural identity that can strengthen a sense of belonging and pride. However, on the other hand, social media also presents challenges, such as cultural homogenisation, threats to local traditions, and reinforcement of negative stereotypes. Conflict and polarisation in online discussions can undermine harmony between cultural communities, while superficial interactions can diminish the value and sustainability of cultural practices. Therefore, users and policymakers need to critically address the role of social media to ensure it supports cultural diversity and progress.